A Study on the Ideal Teachers’ Personality in Relation to Students’ Learning Motivation in Senior High School - Dewi Sartina; Abdul Halim; A. Muliati (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
The objectives of the research are to describe the ideal teachers’ personality as perceived by students, to describe what is students’ motivation in learning English taught by teachers who have this ideal teachers’ personality and to describe a correlation between teacher personality perceived by students and students' learning motivation. This research was designed for descriptive methods with quantitative approaches. The participants of the research were 149 students from MAN 1 Makassar and 4 teachers. They were chosen by cluster random technique. The data were obtained through questionnaires, interviews, and observation. The result of the findings showed that the ideal teachers’ personalities as perceived by students were friendly with (93.95%) positive choice. It equals 139 students along with sincere (93.29%), polite (93.28%), patient (92.62%), good teaching skill or ability (91.95%), organized (89.27%), care or empathy (83.89%), cheerful (83.21%), creative (81.88%) and interesting (81.21%). The findings also showed that most of the motivation of students from MAN 1 Makassar City has motivation between very high, high and medium levels and were motivated by 10 different ideal teachers’ personality such as friendly, caring, organized and so on. On the other hand, there were still some students who have a negative assessment of their teacher. The findings also showed that there was a significant correlation between teachers’ personality and students’ motivation in learning English.